Implementasi Tanggung Jawab Sosial dan Lingkungan pada PT. Indocitra Jaya Samudera Desa Pengambengan Kecamatan Negara Kabupaten Jembrana - DEWAYANTI, LARAS AYU; WIDHIANTINI, WIDHIANTINI; BUDIASA, I WAYAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.10, No.1, Juli 2021, 2021)
Implementation of Corporate Social and Environmental Responsibility at PT. Indocitra Jaya Samudera Pengambengan Village, Negara Sub-district, Jembrana District PT. Indocitra Jaya Samudera is a sardine canning company located in Pengambengan Village, Negara District. In its business activities, the company utilizes fish as natural resources that are processed into canned food. The company's operational processes inevitably impact the environment and surrounding communities. For that reason, the company needs to carry out its socio-environmental responsibilities as regulated in Law 40/2007 on Limited Liability Companies and Financial Services Authority Regulation (POJK) Number 51/POJK.03/2017. This study aims to determine the amount of funds allocated for corporate socio-environmental responsibility programs at PT. Indocitra Jaya Samudera and the extent of corporate socio-environmental responsibility implementation carried out by the company. This research uses descriptive qualitative and quantitative descriptive methods. The results show that the company has allocated funds of less than 1% of the company's budget as a form of corporate’s socio-environmental responsibility with a larger portion of funds allocated for corporate social responsibility. The corporate social responsibility programs include: social assistance programs, educational programs, health programs and religious programs. Whereas programs on environmental responsibility include: environmental care programs, natural disaster response programs and infrastructure improvement programs. This study recommends PT. Indocitra Jaya Samudera form a special division/department to effectively handle and supervise corporate socio-environmental responsibility programs.